Proposta de implementação do orçamento participativo para Instituto Federal Farroupilha - Campus São Vicente do Sul - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This work is centered on how to prepare budgets in the light of current legislation, where we try to use simple language, approaching the theme from the introduction of the Program Budget in Brazil until we arrive at the proposal for the implementation of the Participatory Budget for the Federal Institute of Education, Science and Technology Farroupilha - Campus São Vicente do Sul. The process of democratizing decision-making activities, directly through participatory democracy, goes far beyond budgetary definitions and brings together a process of building citizens' belonging. The objective of the research is to propose an innovation in the process of elaboration of action plans and budget planning, of the IFFAR Campus São Vicente do Sul, based on the principles of participatory democracy through a dialectical method. The implementation of the new methodology is intended to improve budget preparation and execution, improving efficiency, effectiveness and cost effectiveness and assisting in the citizenship education of individuals, encouraging the engagement of the academic community in budget management. In order to achieve the objectives of this project, the research was carried out with the academic community of Campus São Vicente do Sul. This community is formed by a critical and heterogeneous mass of approximately 2 thousand people with diverse characteristics and composed of students, professors, administrative technicians, outsourced workers and representatives of the external community who participate in consultative and/or deliberative councils. This research is framed as an action research, considering that it proposes a resolution to a collective problem. With the application of this research, it was possible to measure the level of interest of the academic community in engaging in the search for solutions to the daily demands that are of interest to the community and, from now on, start the process of creating the feeling of belonging to the common space, not only for pointing out problems or making criticisms, but also for proposing viable technical solutions capable of resolving issues in a perennial way, based on collective construction through the Participatory Budget method. It was also possible to prove, through the present research, that the decisions referring to the budget programming, currently, in Campus São Vicente do Sul, are happening in a centralized way, where the management members decide the direction of the institution, with no mechanisms for the participation open to the academic community.
Keywords: Orçamento; Participação política; Cidadania; Administração pública; IFFAR Campus São Vicente do Sul; Budget; Political participation; CNPQ::CIENCIAS HUMANAS